2009
DOI: 10.4067/s0716-97602009000100009
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effect of Cinnamon extracts against carbon tetrachloride induced oxidative stress and liver injury in rats

Abstract: Cinnamon is used to flavor most foods in Arabian countries. The aim of this study was to evaluate the medicinal importance, reflecting an important trend in research. The hepatoprotective activity of aqueous and ethanolic extracts of cinnamon was investigated against carbon tetrachloride (CCl 4 ) induced lipid peroxidation and hepatic injury in rats. The elevated serum AST and ALT enzymatic activities induced by CCl 4 were significantly restored to near normal by oral administration of 200 mg/kg of either extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
50
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(58 citation statements)
references
References 15 publications
8
50
0
Order By: Relevance
“…Studies have shown that antioxidants and plant extracts can play a protective role in inhibiting pesticide-induced toxicity (65,66) . Our results were in agreement with Moselhy et al (21,58) and Mohamed et al (54) in their study of protective effect of myoporum laetum against oxidative stress induced by profenofos in rats. Results are expressed as mean ± SD for four samples **: Significance at P< 0.02 ***: Significance at P< 0.01…”
Section: Effect On the Activities Of Different Antioxidant Enzymes ( supporting
confidence: 83%
See 3 more Smart Citations
“…Studies have shown that antioxidants and plant extracts can play a protective role in inhibiting pesticide-induced toxicity (65,66) . Our results were in agreement with Moselhy et al (21,58) and Mohamed et al (54) in their study of protective effect of myoporum laetum against oxidative stress induced by profenofos in rats. Results are expressed as mean ± SD for four samples **: Significance at P< 0.02 ***: Significance at P< 0.01…”
Section: Effect On the Activities Of Different Antioxidant Enzymes ( supporting
confidence: 83%
“…The elevated of serum cholesterol and triglycerides were significantly reduced in the animal groups treated with cinnamon extract (Table 9). These results were in agreement with Moselhy and Ali (21) in the study of protective effect of cinnamon on CCl 4 intoxicated rats. …”
Section: Effect On Lipid Profilesupporting
confidence: 82%
See 2 more Smart Citations
“…Various reports have demonstrated that oxidative stress plays a vital role in liver toxicity induced by such substances as alcohol, carbon tetrachloride, chemotherapeutic agents, and acetaminophen (dos Santos et al, 2007;Kostopanagiotou et al, 2009;Moselhy and Ali, 2009;Samuhasaneeto et al, 2009). Reactive oxygen species (ROS), generated during oxidative stress, are extremely reactive and may modify and inactivate cellular lipids, proteins, DNA, and RNA, and thus cause cell damage.…”
Section: Introductionmentioning
confidence: 99%